Low Molecular Weight Apolipoprotein(a) Phenotype Rather Than Lipoprotein(a) Is Associated With Coronary Atherosclerosis and Myocardial Infarction - Afanasieva, Olga I.; Ezhov, Marat V.; Tmoyan, Narek A.; Razova, Oksana A.; Afanasieva, Marina I.; Matchin, Yuri G.; Pokrovsky, Sergei N. (Frontiers in Cardiovascular Medicine, 2022)
Background and aims. Current evidence suggests that lipoprotein(a) [Lp(a)] level above 50 mg/dL is associated with increased cardiovascular risk. Our study aim was to determine the relationship of apolipoprotein(a) [apo(a)] phenotypes and Lp(a) concentration below and above 50 mg/dL with coronary atherosclerosis severity and myocardial infarction (MI). Material and methods. The study population consisted of 540 patients (mean age 54.0±8.8 years, 82% men) who passed through coronary angiography. The number of diseased major coronary arteries assessed atherosclerosis severity. Lipids, glucose, Lp(a) levels and apo(a) phenotypes were determined in all patients. All patients were divided into 4 groups: with Lp(a)<50 mg/dL [“normal” Lp(a)] or ≥50 mg/dL [hyperLp(a)], and with low-molecular (LMW) or high-molecular weight (HMW) apo(a) phenotypes. Results. Baseline clinical and biochemical characteristics were similar between the groups. In groups with LMW apo(a) phenotypes, the odds ratio (OR; 95% confidence interval) of multivessel disease was higher [10.1; 3.1-33.5, p<0.005 for hyperLp(a) and 2.2; 1.0-4.9, p=0.056 for normal Lp(a)], but not in the group with HMW apo(a) and hyperLp(a) [1.1; 0.3-3.3, p=0.92] compared with the reference group with HMW apo(a) and normal Lp(a). Similarly, MI was observed more often in patients with LMW apo(a) phenotype and hyperLp(a) and normal Lp(a) than in groups with HMW apo(a) phenotype. Conclusion. The LMW apo(a) phenotype is associated with the severity of coronary atherosclerosis and MI even when Lp(a) level is below 50 mg/dL. The combination of Lp(a) level above 50 mg/dL and LMW apo(a) phenotype increases the risk of severe coronary atherosclerosis, regardless of other risk factors.